2014
DOI: 10.1097/pas.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Carcinosarcoma With PTCH1 Mutations in Both Epithelial and Sarcomatoid Primary Tumor Components and in the Sarcomatoid Metastasis

Abstract: Basal cell carcinosarcoma is a rare biphenotypic malignant skin tumor, in which one tumor component has light microscopic features of basal cell carcinoma, whereas the other has features of sarcoma. Clinical experience with this tumor is limited, and associated molecular genetic alterations are unknown. Herein, we report a unique case of metastatic basal cell carcinosarcoma, in which we analyzed the 2 components of the primary tumor as well as the metastasis by next-generation sequencing. The patient was a 72-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Mutational analysis by Paniz‐Mondolfi et al confirmed that both elements of cutaneous carcinosarcoma had identical mutations . In addition, Kiuru et al showed that basal cell carcinosarcoma shared identical PTCH1 mutations in both epithelial and sarcomatoid primary tumor components and in the sarcomatoid intraabdominal metastatic tumor . Recently, Harms et al reported that three of four basal cell carcinosarcoma displayed a similar copy number variations and copy‐neutral loss of heterozygosity changes between the epithelial and mesenchymal components within each tumor …”
Section: Discussionmentioning
confidence: 99%
“…Mutational analysis by Paniz‐Mondolfi et al confirmed that both elements of cutaneous carcinosarcoma had identical mutations . In addition, Kiuru et al showed that basal cell carcinosarcoma shared identical PTCH1 mutations in both epithelial and sarcomatoid primary tumor components and in the sarcomatoid intraabdominal metastatic tumor . Recently, Harms et al reported that three of four basal cell carcinosarcoma displayed a similar copy number variations and copy‐neutral loss of heterozygosity changes between the epithelial and mesenchymal components within each tumor …”
Section: Discussionmentioning
confidence: 99%
“…This was highlighted in recent work by Siroy et al Their study of 699 advanced-stage melanomas found significant associations of mutations with clinical subtypes and primary tumor location [53]. Indeed, the authors showed that BRAF V600E mutations were significantly associated with cutaneous and unknown primary melanomas (p<0.001), whereas KIT mutations were significantly associated with acral and mucosal melanomas (p<0.001) [53].…”
Section: -16 Days >Q30mentioning
confidence: 74%
“…Indeed, the authors showed that BRAF V600E mutations were significantly associated with cutaneous and unknown primary melanomas (p<0.001), whereas KIT mutations were significantly associated with acral and mucosal melanomas (p<0.001) [53]. Additionally, BRAF V600E mutations were significantly associated with the trunk location compared with head and neck (p=0.0004), whereas TP53 mutations were significantly associated with head and neck compared with the trunk or extremities (p=0.03 and p<0.0001, respectively) [53].…”
Section: -16 Days >Q30mentioning
confidence: 99%
“…the “conversion theory” suggests that the malignant mesenchymal component derives from the malignant epithelial component during the evolution of the neoplasm . Although different authors have favored different theories, nowadays clearly polarized toward the underlying shared monoclonality, we believe that the histogenetic mechanisms should be better hypothesized depending on each individual case …”
Section: Discussionmentioning
confidence: 93%